The Little Class with the Big Personality : Experiences of Teaching a Class of Young Children with Autism. - Hunnisett, Fran (Jessica Kingsley Publishers, 2004)
The Little Class with the Big Personality is an honest account of the day-to-day challenges faced by the teacher of seven very different autistic children. The author's creative, accessible approach invites the reader to look beyond the stereotypes of mainstream schooling and explore the experience of teaching a lively group of children with autism. The illustrations, by one of the children, add a pupil's perspective of the diverse personalities and class activities described within the book. The author provides an insight into the hopes and concerns of parents as their children begin their ed.